2018
DOI: 10.1159/000495898
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Lipid Droplet Accumulation in Liver Through a SIRT1/ ATF6-Dependent Mechanism

Abstract: Background/Aims: Lipid droplets (LDs) are dynamic organelles that store neutral lipids during times of energy excess, and an increased accumulation of LDs in the liver is closely linked to hepatic steatosis. Our previous studies suggested that resveratrol (RSV) supplement could improve hepatic steatosis, but the underlying mechanism, particularly which related to LD accumulation, has not yet been elucidated. Methods: A high-fat diet (HFD) and palmitic acid were used to induce hepatic steatosis in mouse liver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 75 publications
2
35
0
1
Order By: Relevance
“…RSV (resveratrol) supplementation in rodents fed with a highfat diet demonstrated an increased number of mitochondria and, in particular, an increase in hepatic decoupling protein 2 expression, which could be involved in the normalization of the hepatic fat content [18]. Resveratrol significantly reduced TAG (triacylglycerols) and cholesterol, as well as the number and size of lipid droplets [19,20]. It would appear that a low dose of resveratrol (0.005%) is more effective than higher doses (0.02%) at reducing the development of hepatic steatosis, along with increases in body weight, plasma TAG levels, and total cholesterol levels [21].…”
Section: Steatosismentioning
confidence: 99%
“…RSV (resveratrol) supplementation in rodents fed with a highfat diet demonstrated an increased number of mitochondria and, in particular, an increase in hepatic decoupling protein 2 expression, which could be involved in the normalization of the hepatic fat content [18]. Resveratrol significantly reduced TAG (triacylglycerols) and cholesterol, as well as the number and size of lipid droplets [19,20]. It would appear that a low dose of resveratrol (0.005%) is more effective than higher doses (0.02%) at reducing the development of hepatic steatosis, along with increases in body weight, plasma TAG levels, and total cholesterol levels [21].…”
Section: Steatosismentioning
confidence: 99%
“…When higher concentrations were used, only 10 µM DH-R and 25 µM R-4G induced significant effects. However, several authors have reported positive effects of resveratrol at higher concentrations (10–100 µM) in in vitro assays [ 46 , 47 ]. Indeed, Ji et al (2015) reported a reduction in triglyceride levels in AML12 cells from 25 to 100 μM of resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol induces the expression of adiponectin (one of the adipokines) and improves insulin resistance in adipocytes and inhibits the inflammatory response (Sadruddin and Arora, 2009;Timmers et al, 2011). Resveratrol is specifically known to activate mammalian nicotinamide adenosine dinucleotidedependent deacetylase SIRT1, which is involved in regulating glucose homeostasis, lipid metabolism, and the activation of mitochondrial function (Baur, 2010;Zhou et al, 2018). SIRT1 is a NAD+-dependent protein deacetylase that is a critical regulator of energy homeostasis-dependent nutrient metabolism (Vassilopoulos et al, 2011;Aguilar-Arnal et al, 2016).…”
Section: Resveratrolmentioning
confidence: 99%